Pelatihan E-Commerce sebagai Media Promosi Kain Songket Khas Desa Wisata Sukarara - Lalu Masyhudi; Dyah Indraswati (Pusat Kajian Pariwisata dan Publikasi Jurnal Sekolah Tinggi Pariwisata Mataram, 2023)
Community Service Activities (PKM) in Sukarara tourist village aim to provide skills for Songket craftsmen to be able to promote songket fabrics independently / in groups using e-commerce such as Whatsapp Business, Tiktok Shop, and Instagram. PKM is carried out in the form of training with lectures, discussion, and simulation/practice methods. PKM activities get an output in the form of songket craftsmen can apply e-commerce so that they can help promote Songket fabrics typical of Sukarara tourist village with a wider promotional reach, faster, and increasing profits. Providing new skills to the community, especially Songket craftsmen in promoting songket cloth typical of Sukarara tourism village through e-commerce.